Immunotherapy for prostate cancer: False promises or true hope?. Issue 23 (20th September 2016) - Rekoske, Brian T.; McNeel, Douglas G.
Abstract : Prostate cancer is the most commonly diagnosed cancer, and the second leading cause of cancer‐related death for men in the United States. Despite the approval of several new agents for advanced disease, each of these has prolonged survival by only a few months. Consequently, new therapies are sorely needed. For other cancer types, immunotherapy has demonstrated dramatic and durable treatment responses, causing many to hope that immunotherapies might provide an ideal treatment approach for patients with advanced prostate cancer. However, apart from sipuleucel‐T, prostate cancer has been conspicuously absent from the list of malignancies for which immunotherapies have received recent approval from the US Food and Drug Administration. This has left some wondering whether immunotherapy will "work" for this disease. In this review, the authors describe current developments in immunotherapy, including approaches to engage tumor‐targeting T cells, disrupt immune regulation, and alter the immunosuppressive tumor microenvironment. The authors then describe the recent application of these approaches to the treatment of prostate cancer. Given the Food and Drug Administration approval of 1 agent, and the finding that several others are in advanced stages of clinical testing, the authors believe that immunotherapies offer real hope to improve patient outcomes for men with prostate cancer, especially as investigators begin to explore rational combinations of immunotherapies and combine these therapies with other conventional therapies. Cancer 2016;122:3598‐607. © 2016 American Cancer Society . Abstract : In this review, the authors highlight the history of immunotherapeutic development for prostate cancer and many of the strategies currently being explored. They conclude that immunotherapies have promise for improving clinical outcomes, and that the greatest benefits will come as immunotherapy approaches begin to be rationally combined with other therapies.